(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2003)
A quantitative study of planktonic foraminiferal assemblages has been performed on 7 box cores from different areas of the eastern Mediterranean. This study allowed to reconstruct a high resolution biostratigraphic scheme of the eastern basin for the late Pleistocene/Holocene. In particular, 6 planktonic foraminiferal assemblage zones have been recognized during the last 18 kyrs, based on the most significant assemblage changes. The chronological framework is defined by a well dated tephra level (Z2) and permits to calculate an average sedimentation rate for one of the studied cores (BC19). Similar changes in planktonic foraminiferal assemblages are identifiable in wide areas of the eastern Mediterranean, although records of individual species may show important regional patterns. The comparison between the assemblage zones here defined for the eastern Mediterranean and the existing biozonation for the central Mediterranean shows that similar changes in planktonic microfauna occurred throughout trhe Mediterranean area during the investigated time slice.